Euromaidan and conflict in Eastern Ukraine in social networking sites: Territorial differences of pro-Russian subscriptions in Ukraine - Dobysh, Mykola (Hungarian Geographical Bulletin, 2019)
Securitization of cyberspace is of great geopolitical concern. Behaviour on the Internet is not diminishing the influence of existing borders but can polarize society along territorial divisions. The paper explores territorial differences in the subscription to public pages and open groups in social networking sites (SNS), which emerged as a reaction to revolutionary events in Ukraine (known as Euromaidan or Revolution of Dignity) in 2013–2014 and Russia-backed armed conflict in the East of the country. The findings show differences in subscription to such pages in Vkontakte (the most popular SNS in Ukraine before a ban in 2017) among citizens of Ukraine and Russia, regional centres in Ukraine, cities in uncontrolled by Ukrainian government territories, reclaimed by Ukrainian army territories, territories of Lugansk and Donetsk regions which were not under substantial control of Russia-backed separatists, and peripherial cities of the neighbouring Kharkiv, Dnipropetrovsk, and Zaporizhya oblasts. The paper also analyzes the geopolitical narratives of pro-Russian public pages in Vkontakte and shows how SNS could be used as a geopolitical tool.